FAKTOR PENYEBAB DAN UPAYA PENYELESAIAN KASUS PERTANAHAN DI DESA BILELANDO KECAMATAN PRAYA TIMUR KABUPATEN LOMBOK TENGAH - NOVIE AFIF MAULUDIN (Universitas Mahasaraswati K. Mataram, 2022)
The purpose of this study was to determine the factors causing the occurrence of land cases in Bilelando Village, Praya Timur District, Central Lombok Regency and how to resolve land cases in Bilelando Village, Praya Timur District, Central Lombok Regency. To answer the problem formulation of the author. The research method used is a sociological empirical legal research method in accordance with facts related to people's behavior. And using interview and documentation techniques to obtain data. The data is processed by conducting a qualitative analysis, namely data analysis carried out by understanding and compiling the data that has been collected systematically so that an overview of the problem or situation under study is then presented with descriptive analysis. The results show that 1) Lack of orderly land administration in the past. 2) Lack of attention to administrative processes so that it is easy to be claimed by others. 3) The condition of people who are increasingly aware of and understand their interests and rights. 4) There are still many lands that do not have certificates. And 5) There are parties who use the opportunity to seek material gains unreasonably. Efforts to settle land cases in Bilelando Village, Praya Timur District, Central Lombok Regency are firstly non-litigation or outside the court and secondly litigation or through court.